A novel phage display based platform for exosome diversity characterization. Issue 8 (10th February 2022) - Maisano, Domenico; Mimmi, Selena; Dattilo, Vincenzo; Marino, Fabiola; Gentile, Massimo; Vecchio, Eleonora; Fiume, Giuseppe; Nisticò, Nancy; Aloisio, Annamaria; de Santo, Maria Penelope; Desiderio, Giovanni; Musolino, Vincenzo; et al.
Abstract : We present an innovative approach allowing the identification, isolation, and molecular characterization of disease-related exosomes based on their different antigenic reactivities. Abstract : We present an innovative approach allowing the identification, isolation, and molecular characterization of disease-related exosomes based on their different antigenic reactivities. The designed strategy could be immediately translated into any disease in which exosomes are involved. The identification of specific markers and their subsequent association with exosome subtypes, together with the possibility to engineer target-guided exosome-like particles, could represent the key for the effective adoption of exosomes in clinical practice.